1998
DOI: 10.1007/s002239900390
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density in Children and Adolescents with Diabetes Mellitus Type 1 of Recent Onset

Abstract: There is still controversy over the impact of diabetes control and duration on bone mass and growth parameters in children and adolescents with insulin-dependent diabetes mellitus (IDDM). The aim of this study was to assess bone mineral density (BMD) at axial and appendicular sites, in children with noncomplicated IDDM of recent onset, and its relation to metabolic control and auxological parameters (weight, height, and puberal stage). Fifty-five young Spanish IDDM, otherwise healthy patients (26 males, aged (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
38
3
6

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 22 publications
7
38
3
6
Order By: Relevance
“…Wakasugi et al (14) found no relationship between the level of HbA 1c and deficits in bone mass of type 2 diabetic adults. Pascual et al (15) found no correlation between BMD and HbA 1c in children with type 1 diabetes but acknowledged the fact that HbA 1c may not be an ideal marker for poor glycemic control because it represents only the patients' glycemic status of the last 3 months; it is noteworthy that changes in bone metabolism take place over a longer period. Although IGT (i.e., 2-h glucose Ն140 mg/dl) is an important precursor of diabetes (11), it is difficult to speculate the duration of this condition in our IGT children; nevertheless, we believe that inadequate duration of the pre-diabetic state may have contributed to the lack of significant differences in BMC and BMD of the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Wakasugi et al (14) found no relationship between the level of HbA 1c and deficits in bone mass of type 2 diabetic adults. Pascual et al (15) found no correlation between BMD and HbA 1c in children with type 1 diabetes but acknowledged the fact that HbA 1c may not be an ideal marker for poor glycemic control because it represents only the patients' glycemic status of the last 3 months; it is noteworthy that changes in bone metabolism take place over a longer period. Although IGT (i.e., 2-h glucose Ն140 mg/dl) is an important precursor of diabetes (11), it is difficult to speculate the duration of this condition in our IGT children; nevertheless, we believe that inadequate duration of the pre-diabetic state may have contributed to the lack of significant differences in BMC and BMD of the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Most (27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44), although not all (45,46,47,48,49), studies report a significant decrease in BMD at either the spine, hip or total body. The magnitude of the decrease in BMD varied quite markedly from 8 to 67%, and large gender differences appear to be present, with many studies documenting changes in BMD in either males or females only.…”
Section: Quantitative and Structural Bases Of Bone Fragilitymentioning
confidence: 99%
“…(19) Importantly, the majority of studies on patients with T1DM reported no association between BMD and glycemic control determined by hemoglobin A 1c serum levels. (5,7,8,11,12,14) …”
Section: Epidemiologymentioning
confidence: 99%